Mode identification and seismic study of δ Scuti, the prototype of a class of pulsating stars. Issue 1 (11th May 2021) - Daszyńska-Daszkiewicz, J; Pamyatnykh, A A; Walczak, P; Handler, G; Pigulski, A; Szewczuk, W
ABSTRACT: We present a seismic study of δ Scuti based on a mode identification from multicoulor photometry. The dominant frequency can be associated only with a radial mode and the second frequency is, most probably, a dipole mode. The other six frequencies have more ambiguous identifications. The photometric mode identification provided also some constraints on the atmospheric metallicity [m/H] ≈ +0.5 and microturbulent velocity ξ t ≈ 4 km s −1 . For models reproducing the dominant frequency, we show that only the fundamental mode is possible and the first overtone is excluded. However, the location of δ Scuti near the terminal age main sequence requires the consideration of three stages of stellar evolution. For the star to be on the main sequence, it is necessary to include overshooting from the convective core with a parameter of at least αov = 0.25 at the metallicity greater than Z = 0.019. It turned out that the value of the relative amplitude of the bolometric flux variations (the non-adiabatic parameter f ) is mainly determined by the position of the star in the HR diagram, i.e. by its effective temperature and luminosity, whereas the effect of the evolutionary stage is minor. On the other hand, the convective efficiency in the subphotospheric layers has a dominant effect on the value of the parameter f . Comparing the theoretical and empirical values of f for the radial dominant mode, we obtain constraints on the mixing length parameter αMLT which is less than about 1.0, independently of the adopted opacity data and chemical mixture. This value of αMLT is substantially smaller than for a calibrated solar model indicating rather low to moderately efficient convection in the envelope of δ Scuti.